Lung involvement in children with lysinuric protein intolerance. Issue 2 (22nd October 2014) - Valimahamed‐Mitha, Sarah; Berteloot, Laureline; Ducoin, Héloise; Ottolenghi, Chris; de Lonlay, Pascale; de Blic, Jacques
Abstract: Background and objectives: Lysinuric protein intolerance (LPI) is a rare multisystemic metabolic disease. The objective of the study was to describe presentation and course of lung involvement in a cohort of ten children. Patients and methods: Retrospective review of patients followed at Necker‐Enfants Malades University Hospital between 1980 and 2012 for a LPI. In patients with lung involvement, clinical data, chest radiographs, pulmonary function tests, bronchoalveolar lavages, and lung biopsies were analyzed. The first and last high‐resolution computed tomography (HRCT) were also reviewed. Results: Lung involvement was observed in ten of 14 patients (71 %). Five patients had an acute onset of respiratory symptoms, three had a progressive onset and two were free of symptoms. During the period studied, six patients (60 %) died, all in a context of respiratory failure. Clinical presentation and course were highly variable, even in the same family. HRCT were performed in seven cases, showing in all cases an interstitial pattern and fibrosis in four. All ten patients had pulmonary alveolar proteinosis (PAP) confirmed by histopathological analysis. Five patients had pulmonary fibrosis (at biopsy and/or HRCT scan). Two patients underwent whole lung lavages, without efficiency. Conclusion: PAP is a constant feature in children with LPI and lung involvement. Pulmonary fibrosis is frequent and these two pathologies may develop independently. This study shows the heterogeneity of presentation and outcome. Lung injury could be secondary to impaired phagocytic function and abnormal inflammatory and immune responses intrinsic to the SLC7A7 mutant phenotype. HRCT is recommended to detect lung involvement.